PENGARUH NILAI TAMBAH SEKTOR PERTANIAN TERHADAP PENYERAPAN TENAGA KERJA DI KALIMANTAN TIMUR - Awang Farouk Ishak (Jurnal Agribisnis Indonesia, 2013)
The objective of this study is to analyze the influence of value added of agriculture sector toward labor absorption in East Kalimantan. This study using quantitative and qualitative approaches, based on the secondary panel data in the time series period of 1993-2009. Partial Least Square (PLS) method (smart PLS Computer program) is analyzed in this study. The result indicates that the value added of agriculture sector has positif trend effect towards the labor absorption. The Standardize path coefficient analysis results indicate that the period of 1993-1997 (before crisis), period of 1998-2002 (after crisis and before regional autonomy) and period of 2001-2009 (after regional otonomy) have a significant relationship between the growth of value-added in agricultural sector toward labour absorption  in the Province of East Kalimantan.